Osteosynthesis of Multiple Costal Fractures - Ruiz Liard, Alfredo; Croci, Fabio; Gastambide, Carmelo (Cirugía del Uruguay, 1984)
Based on morphological-mecanlcal functional and evolutiva consideratlons, the authors chose the oste• osynthesis by means of Judet's agraffes for the treat• ment of patlents with thoracic traumatism with mul• tiple costal fractures, accompanied with important de• formation, pain and persistent respiratory insuficiency. They have obtained good results and succeded in preventing eventual sequela of said factors in patients treated by this procedure.